Impact of consumer consumption adjustments on habits and purchase behavior during COVID-19 - Shehla Qaiser; Muhammad Adnan Bashir; Muhammad Sufyan Ramish; Junaid Ansari; Raghava Gundala; Mohammad Ali Bait Ali Sulaiman (Cogent Business & Management, 2023)
AbstractPurchasing and shopping habits have been disrupted due to the COVID-19 pandemic mainly because of the lockdown imposed in the society and social distancing due to which new habits are being developed among consumers. New regulations and procedures will likely affect the way consumers purchase products and avail services, even if consumers return to their old habits. Digital Marketing, Technological Advancement, Changing Demographics, and consumers’ innovative ways of coping with the blurring of work, leisure, and education boundaries as all of these will contribute to the emergence of new habits. A conceptual framework is developed and tested as a result, which reveals the impact of marketing mix adjustments and lifestyle adjustments of consumers upon their habits as well as purchasing behavior during COVID-19. The moderating role of gender and generational age has been employed in this study to get a deeper understanding of the changing buying behavior of consumers during this pandemic. Data has been collected online due to restrictions imposed and the results depicted the significant impact of marketing mix adjustments as well as lifestyle adjustments on the habits and purchase behavior. As for moderating effect gender had no effect except for place and delivery adjustments and generational age had a moderating effect on all but promotional adjustments during COVID-19. Government policy-makers and retail managers should take note of these findings. Studying the consequences of a crisis over time or comparing the effects of multiple crises can help us better understand consumers’ adjustment behavior during a crisis such as the one that has currently been faced. During COVID-19, comparative research between developed and developing countries can be undertaken to compare changing buying behavior and habits among customers of different nature.